DO WE STILL NEED HUMAN IN DIGITAL BANKING? REDESIGN OF ARTIFICIALLY INTELLIGENT DEVICE USE ACCEPTANCE (AIDUA) MODEL MODERATED BY GENDER DIFFERENCES - Kartika, Candra; Santoso, Ignatius Hari (Universitas Nusa Cendana, 2025)
This study modifies and tests the Artificially Intelligent Device Use Acceptability (AIDUA) model in the Indonesian setting to assess consumer acceptability of Artificially Intelligent Devices (AIDs) in digital banking services. The study specifically examines how performance expectancy, hedonic incentive, social influence, and perceived intrusiveness influence users' desire to use AIDs. It also looks at how gender regulates this willingness. 96 legitimate respondents with prior experience with AI-based digital banking services provided data for the study, which used a quantitative explanatory research approach. Both measurement and structural models were evaluated through the use of Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The findings indicate that hedonic motivation, social influence, and perceived intrusiveness significantly affect willingness to use AIDs, while performance expectancy does not. Additionally, gender does not moderate the relationship between the cognitive constructs and behavioral intention. The model explains 94.8% of the variance in users' willingness, suggesting strong explanatory power. The results suggest that, from a practical perspective, financial institutions should place more emphasis on AI interfaces that are emotionally compelling, socially acceptable, and privacy-preserving than just performance advantages. This study contributes to our understanding of AI's adoption in banking and offers valuable insights for developing digital banking systems that are inclusive and trustworthy. Keywords: Social Influence; Performance Expectancy; Perceived Intrusiveness; Hedonic Motivation; Willingness to use AI Device; Digital Banking